Analysis of risk factors associated with the development and postoperative complications of complicated acute appendicitis in elderly patients - Jin, Zhesi; Zhang, Qian; Cai, Huazhong (Frontiers in Surgery, 2025)
ObjectiveBased on an analysis of large-scale retrospective case data, this study aimed to identify the risk factors associated with the development and postoperative complications of complicated acute appendicitis (CAA) in elderly patients (>60 years).MethodsA total of 296 elderly patients diagnosed with acute appendicitis (AA) who underwent appendectomies at our hospital between January 2020 and January 2025 were enrolled in this study. These patients were categorized into either the CAA group (n = 113) or the uncomplicated acute appendicitis (UCAA) group (n = 183), based on the severity of their clinical presentation. Subsequently, univariate and multivariate logistic regression analyses were performed to identify the risk factors associated with the onset of CAA and its postoperative complications.ResultsThe elderly patients in the CAA group exhibited a higher risk of postoperative complications and intensive care unit (ICU) admission, as well as prolonged hospitalization, compared to those in the UCAA group. Preoperative abdominal pain lasting more than 3 days [odds ratio (OR) = 3.159, P = 0.038], the presence of abdominal muscle tension (OR = 2.297, P = 0.007), appendiceal fecalith (OR = 2.697, P = 0.002), temperature ≥ 37.45 °C (OR = 2.968, P = 0.001), neutrophil percentage ≥ 82.7% (OR = 2.593, P = 0.010), and C-reactive protein (CRP) level ≥ 4.3 mg/L (OR = 3.256, P < 0.001) were identified as independent risk factors associated with the development of CAA. The incidence of postoperative complications in the elderly patients in the CAA group was 31%, which was significantly higher than the 6.0% observed in the UCAA group. An analysis based on the data from the patients with CAA indicated that the presence of nausea/vomiting (OR = 3.629, P = 0.033), white WBC ≥ 14.24 × 109/L (OR = 3.825, P = 0.021), neutrophil percentage ≥ 84.3% (OR = 11.165, P = 0.012), and open appendectomy (OR = 5.799, P = 0.002) were independent risk factors for postoperative complications.ConclusionsAbdominal signs and symptoms, the presence of appendicoliths, body temperature, and the levels of neutrophils and CRP were associated with the occurrence of CAA, while surgical approaches and the levels of WBCs and neutrophils were associated with postoperative complications. This study explored the risk factors associated with CAA and its postoperative complications in elderly patients, thereby offering valuable insights for the clinical management and treatment of AA in this population.